Al–TiH2 composite 'particles' as foaming precursors for metallic foams. (August 2015) - Morsi, K.; Daoush, Walid M.
Abstract : This paper describes the production of metallic foam precursors in 'particle' form as opposed to the typical consolidated bulk compacts. Mechanical milling was used to produce coarse composite particles of aluminum and titanium di-hydride as foaming precursors. The effect of foaming temperature on the resulting products is discussed. The porosity content in the particles was found to increase with an increase in temperature. The refined TiH2 particle size due to mechanical milling leads to limited pore sizes in foamed particles.